Awareness of risk factors and early signs of stroke in high risk population of Pune region - Joshi, Hitanshi P.; Bhattad, Radha; Shyam, Ashok K.; Sancheti, Parag K. (International Journal Of Community Medicine And Public Health, 2022)
Background: Knowledge about risk factors and early signs of stroke helps in early intervention and may lead to a better functional outcome for the patient. This study was conducted to assess awareness about stroke in the high risk population of Pune region. Methods: Ethical committee clearance was taken. A total of 180 samples were recruited and written consent was obtained. Data was collected using a close-ended, self made questionnaire, which was face validated, in an interview based format. Collected data was analysed using descriptive statistics. Results: 43.3% participants were fully aware about stroke. 24.2% participants couldn’t identify a single risk factor.79% participants did not have self risk perception about stroke. Only 2.2% participants identified all the signs and symptoms of stroke correctly. 85.4% participants believed that early treatment of stroke increases chances of recovery. Only 32.5% participants would call the ambulance on occurrence of stroke. Awareness about risk factors and early signs of stroke seems to be higher among high risk population belonging to urban areas of Pune region, with higher literacy levels. Conclusions: There is significant lack of awareness about risk factors and early signs of stroke. Public health education seminars should be conducted to increase awareness, especially targeting population at high risk. Outreach to the rural population should be improved.